Synthesis and characterization, novel across adjacent ring formed phthalocyanine - ÖZKAYA, ALİ RIZA (ROYAL SOC CHEMISTRY, 2011)
Novel mononuclear Zn(II) 4, Co(II) 5 and Cu(II) 6 metallophthalocyanines have been synthesized from 4,4'(ethane-1,1-p-phenol-2,2-p-phenoxy) phthalonitrile 3, which can be obtained by the reaction of 4-nitrophthalonitrile 1 with 1,1,2,2-tetrakis(p-hydroxy-phenyl)-ethane 2. The target water-soluble derivatives of 7-9 were acquired from a boiling suspension of the compounds in aqueous 20% KOH solution. The synthesized complexes have been characterized by UV-vis, IR, H-1 NMRand MALDI-TOF-mass spectroscopies. In addition, the geometric and electronic structures of 2-6 were investigated by ab initio/DFT quantum mechanical calculations using the Gaussian 03 program with HF theory at the B3LYP/3-21G level. The redox properties of the complexes 4-6 were examined by cyclic voltammetry on platinum in DMSO/TBAP. These complexes displayed one-electron metallophthalocyanine-based and multi-electron hydroxyphenyl-based redox processes. The effect of temperature on the d.c. conductivity and impedance spectra of spin coated films of compounds were investigated at the temperatures between 300-452 K and in the frequency range of 40-105 Hz. Thermally activated conductivity dependence on temperature was observed for all compounds. A. c. results indicated that conduction mechanism can be explained by classical hopping barriers mechanism for all films.
Keywords: HETERO-DINUCLEAR PHTHALOCYANINES; GAS-SENSING PROPERTIES; ELECTRICAL-PROPERTIES; OXYGEN REDUCTION; SPECTROELECTROCHEMISTRY; ELECTROCHEMISTRY; METALLOPHTHALOCYANINES; SUBSTITUENTS; DERIVATIVES; COBALT(II)